2010
DOI: 10.2139/ssrn.1665005
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Contaminated Site Cleanup Revisited: The Case of Naples and Caserta, Italy

Abstract: Summary Guerriero and Cairns (2009) recently estimate that contaminated sites and improper waste management result in 848 excess deaths per year in the provinces of Naples and Caserta in Southern Italy, 403 of which are fatal cancers. In the absence of estimates of the Value of a Prevented Fatality (VPF) in Italy or specific to the hazardous waste context, they use figures recommended by DG-Environment. Contrary to their claims, estimates of the VPF are available for Italy that are specific to the hazardous wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Using parameters specific to the Italian context, the study concluded that the potential monetary benefits achievable through waste sites cleanup was even greater than that reported by Guerriero and Cairns: €12.936 billion. 34 In both studies, the benefit estimates were considerably higher than the cost, €143 million, agreed by the Government for the remediation of the hazardous waste sites in the two provinces of Caserta and Naples.…”
Section: Evidence From Economic Studies Evaluating the Economic Benefmentioning
confidence: 81%
“…Using parameters specific to the Italian context, the study concluded that the potential monetary benefits achievable through waste sites cleanup was even greater than that reported by Guerriero and Cairns: €12.936 billion. 34 In both studies, the benefit estimates were considerably higher than the cost, €143 million, agreed by the Government for the remediation of the hazardous waste sites in the two provinces of Caserta and Naples.…”
Section: Evidence From Economic Studies Evaluating the Economic Benefmentioning
confidence: 81%